Toward Angiogenesis Inhibitors Based on the Conjugation of Organometallic Platinum(II) Complexes to RGD Peptides - Zamora, Ana; Gandioso, Albert; Massaguer, Anna; Buenestado, Silvia; Calvis, Carme; Hernández, Jose Luis; Mitjans, Francesc; Rodríguez, Venancio; Ruiz, José; Marchán, Vicente (ChemMedChem, 2018)
A novel conjugate between a cyclometalated platinum(II) complex with dual antiangiogenic and antitumor activity and a cyclic peptide containing the RGD sequence (‐Arg‐Gly‐Asp‐) has been synthesized by combining solid‐ and solution‐phase methodologies. Although peptide conjugation rendered a non‐cytotoxic compound in all tested tumor cell lines (± αVβ3 and αVβ5 integrin receptors), the antiangiogenic activity of the Pt‐c(RGDfK) conjugate in human umbilical vein endothelial cells at sub‐cytotoxic concentrations opens the way to the design of a novel class of angiogenesis inhibitors through conjugation of metallodrugs with high antiangiogenic activity to cyclic RGD‐containing peptides or peptidomimetic analogues. Platinum‐backed peptides: Conjugates of cyclometalated platinum(II) complexes and RGD peptides are investigated as potential angiogenesis inhibitors. The antiangiogenic activity of the Pt‐c(RGDfK) conjugate in human umbilical vein endothelial cells at sub‐cytotoxic concentrations opens the way to the design of angiogenesis inhibitors through conjugation of metallodrugs with high antiangiogenic activity to cyclic RGD‐containing peptides or peptidomimetic analogues.